High-strength, corrosion-resistant and high-fatigue cast aluminum alloy and preparation method and application thereof

By controlling the components and heat treatment processes of aluminum alloys, the problem of existing aluminum alloys being difficult to meet high strength, corrosion resistance and fatigue resistance at the same time is solved, and the synergistic improvement of these properties is achieved, and recycling and low-carbon manufacturing is supported.

CN119710381APending Publication Date: 2025-03-28WEIQIAO LIGHTWEIGHT RESEARCH CENTER AT SOOCHOW +1

Patent Information

Application Number
CN202411902152.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing aluminum alloys are difficult to meet the requirements of high strength, corrosion resistance and high fatigue resistance at the same time, especially in the field of automotive chassis parts, and have low tolerance for Fe impurities, which limits recycling and low-carbon manufacturing.

Method used

By controlling the specific components and their content of aluminum alloy, especially Cu content, and using sectional heating heat treatment during the preparation process, the heating rate of different temperature intervals is adjusted to improve the phase composition of aluminum alloy and improve its strength, corrosion resistance and fatigue resistance.

Benefits of technology

The high strength, corrosion resistance and fatigue resistance of aluminum alloys are achieved, which can meet the strict service requirements of chassis structural castings, and improve the tolerance for Fe impurities, supporting recycling and low-carbon manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710381A_ABST
    Figure CN119710381A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy and a preparation method and application thereof, the cast aluminum alloy comprises Al, Si, Cu, Mg, Mn, Ti, Cr, Sr and inevitable impurities, and the impurities comprise Fe and other impurities except Fe; the proportion of Cu is controlled, during preparation, all the components are mixed, melted and refined to prepare an aluminum alloy cast ingot, and then the aluminum alloy cast ingot is subjected to heat treatment, quenching cooling and aging treatment; the heat treatment is carried out in different temperature intervals according to different heating rates. The cast aluminum alloy has the characteristics of high strength, corrosion resistance and high fatigue, and can meet the strict service requirements of chassis structural castings; and moreover, the tolerance to impurity elements, especially iron, is high, so that the flat-grade and even upgraded use of a large number of high-quality recycled aluminum alloys can be met, the aluminum alloy can be recycled, and carbon emission is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cast aluminum alloys, and in particular to a high-strength, corrosion-resistant, high-fatigue cast aluminum alloy and a preparation method and application thereof. Background Art

[0002] In recent years, with the increasing demand for energy conservation, emission reduction, and carbon reduction, new energy vehicles have developed rapidly. In order to increase driving range and reduce manufacturing costs, automobile lightweighting has achieved rapid development. Automobile chassis parts have become an important field of lightweight development due to their outstanding weight reduction benefits. However, the service conditions of chassis parts are very harsh. They not only need to withstand extreme load conditions, but also always withstand alternating loads during the entire service process. They also need to resist the erosion of complex atmosphere environments. Therefore, the alloys used in the system must have strength, fatigue and corrosion resistance. Aluminum-silicon casting alloys have been widely used in automobile manufacturing due to their low density, excellent strength, good casting performance, and corrosion resistance. Among them, chassis structural parts of passenger cars and commercial vehicles are increasingly made of aluminum-silicon casting alloys to achieve lightweighting. However, in order to simultaneously meet multiple service conditions, chassis structural parts currently mainly use A356 and its modified alloys with medium strength, corrosion resistance and medium fatigue performance, which limits the further weight reduction of the next generation of chassis structural castings. There is an urgent need to develop new high-strength, corrosion-resistant and high-fatigue casting aluminum alloys; and due to the low Fe impurity tolerance of this series of alloys, it is difficult to achieve horizontal recycling, and it will be difficult to achieve low-carbon emissions in the manufacturing process in the future. There is an urgent need to develop a renewable alloy system under high performance requirements.

[0003] Although A356 and its modified alloys, which are currently used in mainstream chassis structural parts, have excellent corrosion resistance, their strength and fatigue resistance are not high enough. In addition, the A356 series alloys have a low tolerance for Fe impurities, making it difficult to recycle and reuse aluminum alloys.

[0004] Patent CN 202410003834.1 discloses a cast aluminum alloy, which has excellent heat resistance and can be used at higher service temperatures. It also has high fatigue resistance. However, the corrosion resistance of the aluminum alloy is insufficient and cannot be used in the field of automotive chassis parts.

[0005] That is, in the prior art, it is difficult to obtain an aluminum alloy that has corrosion resistance, high strength, high fatigue strength and toughness and can be used for automobile lightweighting, especially in the field of automobile chassis parts. Summary of the invention

[0006] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved aluminum alloy that has high strength, corrosion resistance and high fatigue resistance and can meet the stringent service requirements of chassis structure castings.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A cast aluminum alloy, comprising Al, Si, Cu, Mg, Mn, Ti, Cr, Sr and inevitable impurities, wherein the impurities include Fe and other impurities except Fe,

[0009] In terms of mass percentage, the cast aluminum alloy comprises: Si 3%-9%, Cu 0.1%-0.45%, Mg 0.1%-0.5%, Mn 0.05%-0.4%, Cr 0.05%-0.3%, Ti 0.05%-0.3%, Sr 0.005%-0.04%, Fe is less than or equal to 0.5%, and the sum of other impurities except Fe is not more than 0.2%. The Al content is adjusted so that the total amount of the aluminum alloy is 100%.

[0010] The process of preparing the cast aluminum alloy includes the steps of mixing and melting the components and then refining them, then making an aluminum alloy ingot, and heat treating the aluminum alloy ingot; the heat treatment is carried out from room temperature to an end temperature, and the end temperature is 515-540°C; and when the temperature is from room temperature to 250°C, the heating rate is controlled to be 0.5-10°C / min; when the temperature is from 250°C to 325°C, the heating rate is controlled to be 0.1-1.25°C / min; when the temperature is from 325°C to 450°C, the heating rate is controlled to be 0.1-2°C / min; when the temperature is from 450°C to the end temperature, the heating rate is controlled to be 0.5-10°C / min.

[0011] In the prior art, although A356 and its modified alloys used in mainstream chassis structural parts have excellent corrosion resistance, their strength is not high enough, and their fatigue resistance is not high enough. In addition, the tolerance of A356 series alloys to Fe impurities is low, making it difficult to recycle aluminum alloys. Other existing aluminum alloys have excellent heat resistance and can be used at higher service temperatures. They also have high fatigue resistance, but their corrosion resistance is not enough and cannot be used in the field of automobile chassis parts. The inventors of this application have found through research that by controlling the specific components and contents of aluminum alloys, especially the content of Cu, and when preparing aluminum alloys, the heat treatment step adopts segmented heating, and different heating rates are used in different temperature ranges. By combining fast and slow heating rates in different stages, the phase composition of aluminum alloys can be improved to achieve high strength, corrosion resistance and high fatigue resistance. In the process of heating from 250°C to 325°C, the interior of α-Al grains can promote the interdendritic diffusion of Mg and Si elements to reduce the interdendritic segregation of Mg and Si elements, and form Mg and Si precipitation phases as the nucleation substrate of α-type dispersed phases.

[0012] In some embodiments, during the preparation of the cast aluminum alloy, the heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 250°C to 325°C, and the heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 325°C to 450°C. That is, the heating rate in the fourth section is controlled to be greater than that in the second and third sections, thereby further improving the strength, corrosion resistance and fatigue resistance of the cast aluminum alloy product.

[0013] In some embodiments, in the casting aluminum alloy, Fe accounts for 0.1%-0.5% by mass.

[0014] In some embodiments, some components including Al in the cast aluminum alloy are added by adding recycled aluminum alloy, and the recycled aluminum alloy is a combination of one or more selected from Al-Si-Mg alloy, Al-Si-Cu alloy, Al-Si-Cu-Mg alloy, and Al-Mn alloy.

[0015] The use of recycled aluminum usually leads to an increase in the content of impurity elements in the alloy, especially Fe. The needle-shaped Fe phase formed after solidification will seriously split the matrix. However, the cast aluminum alloy of the present invention has a high tolerance for impurity elements, especially iron, which can not only meet the level and even upgrade use of a large number of high-quality recycled aluminum alloys, but also can be recycled (i.e., regenerated) to reduce carbon emissions. Recycled aluminum alloys can be used in raw materials.

[0016] In some embodiments, the cast aluminum alloy further comprises Zr, and after the heat treatment, the interior of the alloy α-Al grains comprises (Al, Si) 3 (Zr) and (Al, Si) 3 (Zr, Ti) dispersed phases.

[0017] In some embodiments, Zr accounts for 0.05%-0.3% by mass in the cast aluminum alloy.

[0018] In some embodiments, the cast aluminum alloy further includes X1, and X1 is Sn and / or In.

[0019] In some embodiments, in the cast aluminum alloy, the content of the elements contained in X1 is independently 0.001%-0.2% by mass percentage.

[0020] In some embodiments, the cast aluminum alloy further includes X2, wherein X2 is a combination of one or more selected from Mo, V, Y and Er.

[0021] In some embodiments, in the cast aluminum alloy, the content of the elements contained in X2 is independently 0.01%-0.3% by mass percentage.

[0022] In some embodiments, the alloy structure of the cast aluminum alloy includes rose-shaped α-Al grains, dendritic α-Al grains, micron-sized spherical eutectic silicon particles, micron-sized granular iron-containing intermetallic compounds, and micron-sized Chinese character-shaped iron-containing intermetallic compounds;

[0023] The rose-shaped α-Al grains and dendrite-shaped α-Al grains contain α-type dispersed phases with a size of 50 to 500 nm, rod-shaped Al3M-type dispersed phases with a diameter of 20 to 50 nm, and β″ phases, β′ phases and Q′ phases that are coherent or semi-coherent with the matrix;

[0024] The sizes of the micron-sized granular iron-containing intermetallic compound and the micron-sized Chinese character-shaped iron-containing intermetallic compound are both 2 μm to 25 μm.

[0025] In some embodiments, the cast aluminum alloy has a yield strength of 270-290 MPa, a tensile strength of 330-360 MPa, and an elongation after fracture of 8%-12% at room temperature.

[0026] In some embodiments, under the test conditions of smooth specimen, stress ratio R of -1, and 10 million cycles, the fatigue strength of the cast aluminum alloy is 110-120 MPa.

[0027] In some embodiments, the process of preparing the cast aluminum alloy further includes the step of heating to the endpoint temperature and then maintaining the temperature at the endpoint temperature for 4-16 hours.

[0028] The present invention also provides a method for preparing the aforementioned cast aluminum alloy, the preparation method comprising:

[0029] The ingredients are prepared according to the composition, melted, refined, metamorphosed and refined to form an aluminum alloy ingot, and the aluminum alloy ingot is subjected to heat treatment, quenching cooling and aging treatment; wherein the heat treatment is carried out from room temperature to the end temperature, and the end temperature is 515-540°C; and from room temperature to 250°C, the heating rate is controlled to be 0.5-10°C / min; from 250°C to 325°C, the heating rate is controlled to be 0.1-1.25°C / min; from 325°C to 450°C, the heating rate is controlled to be 0.1-2°C / min; from 450°C to 520°C, the heating rate is controlled to be 0.5-10°C / min; from 450°C to the end temperature, the heating rate is controlled to be 0.5-10°C / min.

[0030] In some embodiments, the heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 250°C to 325°C, and the heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 325°C to 450°C.

[0031] In some embodiments, after the temperature is raised to the endpoint temperature, the temperature is maintained at the endpoint temperature for 4-16 hours, and then the quenching cooling is performed.

[0032] In some embodiments, the quench cooling is cooling to room temperature in water within 30 seconds.

[0033] In some embodiments, the aging treatment is performed at 140-200° C. for 6-18 hours.

[0034] In some embodiments, in the process of preparing the cast aluminum alloy, high-quality recycled aluminum alloys such as Al-Si-Mg, Al-Si-Cu, Al-Si-Cu-Mg, Al-Mn, etc. can be melted first, the surface scum is removed, the composition mushroom sample is cast, the composition is measured, and the alloy composition is adjusted to the target range using pure alloys or intermediate alloys of corresponding elements, refined and slag-removed, modified and refined, and allowed to stand for cooling to make aluminum alloy ingots.

[0035] Furthermore, the melting temperature of the Al-Si-Mg, Al-Si-Cu, Al-Si-Cu-Mg, and Al-Mn high-quality recycled aluminum alloys is controlled to be 730-760°C.

[0036] In some embodiments, when the raw material contains recycled aluminum alloy, the preparation method includes the following steps:

[0037] 1) High temperature melting of aluminum alloy: according to the composition ratio requirements of the raw materials, melt high-quality recycled aluminum alloys containing Al-Si-Mg, Al-Si-Cu, Al-Si-Cu-Mg, Al-Mn, etc., control the melting temperature to 730-780℃, and stir for 1-10min until the composition is uniform;

[0038] 2) Casting component mushroom samples, and calculating the mass of the corresponding alloy elements based on the test results;

[0039] 3) Alloying of aluminum alloy melt: scrape off the scum on the surface of the melt, add the pure alloy or intermediate alloy of the corresponding element to the alloy melt prepared in step 1) (note that when adding pure Mg and selective X1, wrap it with aluminum foil to reduce burning loss), control the processing temperature to 720-740°C, stir for 1-10 minutes until the melt composition is uniform, continue to cast the mushroom sample, and adjust it to the target composition range according to the test results;

[0040] 4) Modification and refinement: First, add AlSr10 modifier in an amount such that the Sr element content accounts for 0.005%-0.04% of the weight of the alloy melt; let it stand, then add TCB grain refiner accounting for 0.3%-0.8% of the weight of the alloy melt, and skim the slag to obtain the target aluminum alloy melt;

[0041] 5) Melt refining and slag removal: the melt obtained in step 4) is refined and slag removed by adding a universal refining agent using a rotary argon injection process; the slag is removed after standing;

[0042] 6) Casting: Aluminum alloy melt is cast;

[0043] 7) Heat treatment: The alloy obtained in step 6) is heat treated at room temperature to 540° C. The heat treatment is performed at different temperature ranges and at different heating rates, specifically including:

[0044] The heating rate from room temperature to 250°C is 0.5-10°C / min;

[0045] The heating rate from 250℃ to 325℃ is 0.1~1.25℃ / min;

[0046] The heating rate from 325℃ to 450℃ is 0.1~2℃ / min;

[0047] The heating rate from 450℃ to 520℃ is 0.5~10℃ / min;

[0048] The heating rate from 520°C to 540°C is 0.01-0.2°C / min.

[0049] During the heating process from 250°C to 325°C, the interior of the α-Al grains can promote the interdendritic diffusion of Mg and Si elements to reduce the interdendritic segregation of Mg and Si elements, and form a precipitated phase containing Mg and Si as the nucleation substrate for the α-type dispersed phase.

[0050] 8) Quenching and cooling: the alloy obtained after the four-stage solid solution treatment is cooled to room temperature in water within 30 seconds;

[0051] 9) Aging treatment: The alloy obtained after quenching is kept at 140-200°C for 6-18h.

[0052] The present invention also provides the use of the aforementioned cast aluminum alloy in the preparation of automobile chassis structural parts, engines or transmission components.

[0053] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0054] The aluminum alloy of the present invention achieves a synergistic improvement in strength and fatigue performance while maintaining good corrosion resistance, and can be produced in a low-carbon manner, thereby helping to further lightweight the next generation of chassis structural parts.

[0055] The aluminum alloy of the present invention can combine high strength, corrosion resistance and high fatigue resistance, can meet the stringent service requirements of chassis structure castings, and has a high tolerance to impurity elements, especially iron. It can not only meet the needs of the existing large amount of high-quality recycled aluminum alloys at the same level or even upgraded use, but can also be recycled itself to reduce carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 It is the microstructure diagram of comparative example 3;

[0057] Figure 2 It is the microstructure diagram of comparative example 7;

[0058] Figure 3 is the microstructure diagram of Example 4;

[0059] Figure 4 This is the diffuse phase (transmission electron microscope) image of Example 4;

[0060] Figure 5 is the precipitation strengthening phase (transmission electron microscope) image of Example 4;

[0061] Figure 6 This is the dispersion phase diagram of Example 9. DETAILED DESCRIPTION

[0062] The present invention is based on the fact that the existing cast aluminum-silicon alloys cannot meet the performance requirements of high strength, corrosion resistance and high fatigue at the same time, and there is a contradiction that it is difficult to achieve both strength improvement and corrosion resistance. The strength of the cast aluminum alloy is improved but the fatigue performance is not significantly improved, and the low impurity element content limits the use of high-quality recycled aluminum and other multiple pain points. After a large number of experimental studies, it was unexpectedly found that the use of Al-Si-Mg as the main alloy system, supplemented by trace Cu addition, can achieve the synergistic unity of strength and corrosion resistance. On this basis, Mn and Cr trace elements are added, and the addition amount of each component is controlled, that is, a high tolerance to impurity elements, especially Fe, can be achieved. Not only can the Fe phase morphology be regulated and its harm to the plasticity of the alloy be reduced, but also a uniformly distributed submicron dispersed phase can be formed inside the matrix through a specially designed continuous heat treatment, which synergistically improves the fatigue performance of the alloy, so that the alloy system of the present invention can be prepared using recycled materials, which is suitable for the same level or even upgraded use of recycled materials, saving costs and greatly reducing carbon emissions.

[0063] Furthermore, when a trace amount of Mo element is introduced into the alloy system, the iron phase can be further regulated and the size of the iron-rich phase can be refined; further, when a trace amount of Zr, V, Y, Er and other elements are added into the alloy system, a submicron dispersed phase with a higher number density can be introduced into the matrix without forming a harmful primary phase, thereby improving the fatigue performance of the alloy; further, after Sn and / or In elements are added into the system, it can be found that they can diffuse rapidly and preferentially combine with vacancies, further increasing the nucleation density of the dispersed phase, making the dispersed phase more fine and uniformly distributed. In particular, compared with the existing patented alloys disclosed in the art, the present invention achieves the coordinated unification of high strength, toughness, corrosion resistance and high fatigue performance, solves the long-standing pain point problem of the difficult-to-reconcile strength, toughness, corrosion resistance and fatigue performance of cast aluminum alloys for automobile chassis, has a simple production process, is suitable for industrial mass production, and has great application potential in automobile chassis structural parts and other similar application scenarios.

[0064] In the present invention, through the continuous heat treatment method of controlling the heating rate in different temperature intervals, the temperature is quickly increased from room temperature to 250°C, which can reduce the uneven precipitation of the Mg2Si non-equilibrium phase caused by the solute segregation of Mg and Si elements; the temperature is slowly increased from 250°C to 325°C, which gives full play to the diffusion capacity of Mg and Si elements at higher temperatures, weakens the degree of dendrite segregation, promotes the full precipitation of the Mg2Si equilibrium phase in the crystal, and improves the uniformity of the distribution of the precipitated phase. The precipitated phase can serve as the nucleation base point of the α-type dispersed phase containing Mn, Cr, and Mo elements and the Al3M (M can be Ti, Zr, V, Y, Er, etc.) type dispersed phase, thereby improving the uniformity of the distribution of the dispersed phase; the temperature is slowly increased from 325°C to 450°C, Ensure that the aforementioned α-type dispersed phase and Al3M dispersed phase are fully nucleated on the precipitated β equilibrium phase substrate and grow to a relatively stable size to obtain the dispersed phase with the required volume fraction and number density; quickly heat up from 450°C to 500°C to quickly reach the dissolution temperature required for the β, Q solidification phases and Mg2Si equilibrium phase in the eutectic region, and reduce the growth degree of the dispersed phase in this temperature range; slowly heat up from 500°C to 540°C to successively dissolve the Q phase and β phase, so that a supersaturated solid solution of Si, Mg, and Cu is formed in the alloy α-Al grains, providing composition conditions for subsequent aging strengthening. In addition, within this temperature range, the eutectic silicon phase is spheroidized, and the Chinese character-shaped iron-containing metal compound is discontinuous, which plays an important role in further improving the toughness of the alloy.

[0065] Quenching cooling can maintain the vacancy concentration during solution treatment and obtain a supersaturated solid solution; aging treatment can promote the formation of β″ phase, β′ phase and Q′ phase that are coherent or semi-coherent with the matrix, thereby improving the room temperature strength of the alloy.

[0066] Mg and Cu are the main strengthening elements in Al-Si cast aluminum alloys. By adjusting the content and ratio of Mg and Cu elements, the density of the types of precipitated strengthening phases in the alloy can be controlled to obtain alloys with different strength grades. However, excessive addition of Cu elements is accompanied by a decrease in corrosion resistance. Mg elements have a significant strengthening effect in Al-Si alloys and are usually used as the main strengthening element, but excessive content will greatly reduce the plasticity of the alloy.

[0067] The inventors of the present application have found through research (which has also been verified by multiple embodiments of the present invention) that the addition of a trace amount of Cu element achieves a significant improvement in the strength of the alloy with Mg as the main strengthening element, while having no significant effect on the corrosion performance of the alloy. Therefore, the alloy of the present invention uses Mg as the main strengthening element and a trace amount of Cu to regulate the precipitation of strengthening phases, achieving the synergistic unity of high strength and corrosion resistance.

[0068] The present invention has been found through sufficient experimental verification that the trace addition of Mn and Cr elements effectively realizes the morphology regulation of iron-containing intermetallic compounds in the alloy and significantly improves the toughness of the alloy. This effect is still obvious even when the Fe content is as high as 0.5%, and the strength and elongation of the alloy are maintained at a high level; in addition, with the trace addition of Mn and Cr elements, the fatigue performance of the alloy is significantly improved.

[0069] Through some embodiments of the present invention, it is found that after adding trace Cu elements, the average size of the α-dispersed phase in the alloy is reduced, the number density is increased, and the fatigue strength is significantly higher than that of the alloy without adding trace Cu elements. This rule is maintained in the process of adding Mo and V elements in combination. With the addition of Mo and V elements, some iron-containing intermetallic compounds are transformed into fine spherical particles.

[0070] In some embodiments of the present invention, it is found that after adding a trace amount of Zr element on the basis of adding Mn and Cr microalloying elements, a new rod-shaped (Al, Si) 3 (Zr, Ti) dispersed phase is formed inside the alloy, and the size of this dispersed phase is smaller than the α-dispersed phase, and the number density is also higher. When the Zr addition amount is controlled within a certain value, it can ensure that the strength and toughness of the alloy do not change significantly, but the fatigue performance of the alloy is significantly improved. After exceeding a certain content, the strength and toughness of the alloy are significantly degraded. Further, after adding V, Er, and Y elements in a trace amount to the alloy, the number density of the rod-shaped Al3M (M includes a combination of one or more of Zr, V, Er, and Y) dispersed phase inside the alloy continues to increase. When the addition amount exceeds a certain content, the strength and toughness of the alloy are significantly degraded. Further, when a very small amount of Sn and / or In is added to the alloy, the number density of the α-dispersed phase and Al3M inside the alloy continues to increase, and better fatigue performance is obtained.

[0071] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0072] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0073] Embodiment 1:

[0074] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The content of each element in the cast aluminum alloy is shown in Table 1 below, in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0075] (2) The specific smelting steps of the alloy in this example include:

[0076] The weighed A356.2 alloy, Cu wire, AlMn10, AlCr10 and AlTi10 master alloys were melted at a melting temperature of 760°C. After all were melted, pure Mg blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 730°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 730°C, the F-228 general refining agent was added to the alloy melt by rotary argon injection method for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting molding process used was gravity casting, and the melt was cast into a metal mold preheated to 200°C to prepare castings. Heat treatment process used for ingot casting:

[0077] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 5°C / min;

[0078] The heating rate from 250°C to 325°C is 0.3°C / min;

[0079] The heating rate from 325°C to 450°C is 0.5°C / min;

[0080] Heating rate from 450°C to 530°C is 3.5°C / min), and then kept at 530°C for 6h;

[0081] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0082] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0083] Embodiment 2:

[0084] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The content of each element in the cast aluminum alloy is shown in Table 1 below, in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0085] (2) The specific smelting steps of the alloy in this example include:

[0086] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlMn10 and AlCr10 master alloys were melted at a melting temperature of 760°C. After all were melted, pure Mg blocks and Sn blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting molding process used was gravity casting, and the melt was cast into a metal mold preheated to 200°C to prepare castings. Heat treatment process used for ingot casting:

[0087] Continuously increase the temperature from room temperature to 525°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0088] The heating rate from 250°C to 325°C is 0.15°C / min;

[0089] The heating rate from 325°C to 450°C is 0.2°C / min;

[0090] Heating rate from 450°C to 525°C is 5°C / min), and then kept at 525°C for 8h;

[0091] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0092] The heat treatment method of the cast aluminum alloy comprises:

[0093] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0094] Embodiment 3:

[0095] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0096] (2) The specific smelting steps of the alloy in this example include:

[0097] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10 and AlCr10 master alloys are melted at a melting temperature of 760°C. After all are melted, pure Mg blocks, Sn blocks and In blocks wrapped in aluminum foil are added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt is cooled to 740°C and AlSr10 master alloy is added to cast the mushroom sample. After the composition is qualified, Al-Ti-CB refiner is added and stirred evenly. The amount of refiner added is 3‰ of the melt mass. At 735°C, the rotary argon injection method is used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added is 0.15% of the weight of the alloy melt. After treatment, it is left to stand for 5 minutes, cooled to 700°C, slag is removed, and then cast. The casting process used is gravity casting, and the melt is cast into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is: continuously heating from room temperature to 535°C (specifically: the heating rate from room temperature to 250°C is 5°C / min;

[0098] The heating rate from 250°C to 325°C is 0.15°C / min;

[0099] The heating rate from 325°C to 450°C is 0.2°C / min;

[0100] Heating rate from 450°C to 535°C is 5°C / min), and then kept at 535°C for 6h;

[0101] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 180°C for 6 hours, and after cooling, samples are taken from the ingot for microstructure observation and performance testing.

[0102] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0103] Embodiment 4:

[0104] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0105] (2) The specific smelting steps of the alloy in this example include:

[0106] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10 and AlZr10 master alloys are melted at a melting temperature of 760°C. After all are melted, pure Mg blocks and Sn blocks wrapped in aluminum foil are added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt is cooled to 738°C and AlSr10 master alloy is added to cast the mushroom sample. After the composition is qualified, Al-Ti-CB refiner is added and stirred evenly. The amount of refiner added is 3‰ of the melt mass. At 730°C, the rotary argon injection method is used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added is 0.15% of the weight of the alloy melt. After treatment, it is left to stand for 5 minutes, cooled to 700°C, slag is removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0107] Continuously increase the temperature from room temperature to 525°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0108] The heating rate from 250°C to 325°C is 0.15°C / min;

[0109] The heating rate from 325°C to 450°C is 0.2°C / min;

[0110] Heating rate from 450°C to 525°C is 5°C / min), and then kept at 525°C for 8h;

[0111] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0112] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0113] Embodiment 5:

[0114] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0115] (2) The specific smelting steps of the alloy in this example include:

[0116] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10, AlZr10 and AlMo10 master alloys were melted at a melting temperature of 780°C. After all were melted, the temperature was lowered to 740°C, and pure Mg blocks wrapped in aluminum foil were added and stirred manually for 2 minutes to make the composition uniform, and then allowed to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the component mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was allowed to stand for 5 minutes, cooled to 700°C, and then the slag was removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0117] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0118] The heating rate from 250°C to 325°C is 0.15°C / min;

[0119] The heating rate from 325°C to 450°C is 0.2°C / min;

[0120] Heating rate from 450°C to 530°C is 5°C / min), and then kept at 530°C for 8h;

[0121] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0122] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0123] Embodiment 6:

[0124] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0125] (2) The specific smelting steps of the alloy in this example include:

[0126] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10 and AlV5 master alloys were melted at a melting temperature of 760°C. After all were melted, the temperature was lowered to 735°C, pure Mg blocks and Sn blocks wrapped in aluminum foil were added, and the mixture was stirred manually for 2 minutes to make the composition uniform, and then allowed to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the F-228 general refining agent was added externally to the alloy melt for refining and slag removal by the rotary argon injection method. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was allowed to stand for 5 minutes, cooled to 700°C, and then the slag was removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0127] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0128] The heating rate from 250°C to 325°C is 0.15°C / min;

[0129] The heating rate from 325°C to 450°C is 0.2°C / min;

[0130] Heating rate from 450°C to 530°C is 5°C / min), and then kept at 530°C for 8h;

[0131] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0132] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0133] Embodiment 7:

[0134] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0135] (2) The specific smelting steps of the alloy in this example include:

[0136] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10, AlZr10 and AlV5 master alloys were melted at a melting temperature of 760°C. After all were melted, the temperature was lowered to 735°C, and pure Mg blocks and Sn blocks wrapped in aluminum foil were added, and stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0137] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0138] The heating rate from 250°C to 325°C is 0.15°C / min;

[0139] The heating rate from 325°C to 450°C is 0.2°C / min;

[0140] Heating rate from 450°C to 530°C is 5°C / min), and then kept at 530°C for 8h;

[0141] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0142] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0143] Embodiment 8:

[0144] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0145] (2) The specific smelting steps of the alloy in this example include:

[0146] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10, AlZr10, AlY10 and AlEr10 master alloys were melted at a melting temperature of 760°C. After all were melted, the temperature was lowered to 730°C, and pure Mg blocks wrapped in aluminum foil were added and stirred manually for 2 minutes to make the composition uniform, and then allowed to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the F-228 general refining agent was added externally to the alloy melt for refining and slag removal by the rotary argon injection method. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was allowed to stand for 5 minutes, cooled to 700°C, slag was removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0147] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0148] The heating rate from 250°C to 325°C is 0.15°C / min;

[0149] The heating rate from 325°C to 450°C is 0.2°C / min;

[0150] Heating rate from 450°C to 530°C is 5°C / min), and then kept at 530°C for 8h;

[0151] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0152] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0153] Embodiment 9:

[0154] This example provides a high-strength, corrosion-resistant and high-fatigue cast aluminum alloy. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, measured in percentage by mass. The remainder is Al and other inevitable impurities except Fe.

[0155] (2) The specific smelting steps of the alloy in this example include:

[0156] The weighed pure aluminum ingots, metal silicon, Cu wire, AlTi10, AlFe10, AlMn10, AlCr10, AlZr10 and AlV5 master alloys were melted at a melting temperature of 760°C. After all were melted, the temperature was lowered to 735°C, and pure Mg blocks and Sn blocks wrapped in aluminum foil were added, and stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 740°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 735°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting process used is gravity casting, where the melt is poured into a metal mold preheated to 200°C to prepare the casting. The heat treatment process used for the ingot is:

[0157] Continuously increase the temperature from room temperature to 530°C (specifically: the heating rate from room temperature to 250°C is 4°C / min;

[0158] The heating rate from 250°C to 325°C is 0.15°C / min;

[0159] The heating rate from 325°C to 450°C is 0.2°C / min;

[0160] Heating rate from 450°C to 530°C is 5°C / min), and then kept at 530°C for 8h;

[0161] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0162] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0163] Comparative Example 1:

[0164] Comparative Example 1 uses the commonly used alloy A356.2 for chassis structure castings currently in service. The contents of various elements in the cast aluminum alloy are shown in Table 1 below, in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0165] The specific preparation steps include the following:

[0166] (1) The raw materials of the alloy in this example come from the commonly used alloy A356.2 for chassis structure castings in service, and its composition mass ratio is shown in Table 1;

[0167] (2) The specific smelting steps of the alloy in this example include:

[0168] The weighed A356.2 alloy is melted at a melting temperature of 760°C. After all of it is melted, stir it manually for 2 minutes to make the composition uniform, and let it stand and keep warm for 10 minutes. Cool the melt to 730°C and add AlSr10 intermediate alloy, cast the mushroom sample, and after the composition is qualified, add Al-Ti-CB refiner and stir evenly. The amount of refiner added is 3‰ of the mass of the melt. At 730°C, the rotary argon injection method is used, and F-228 general refining agent is added externally to the alloy melt for refining and slag removal. The amount of refining agent added is 0.15% of the weight of the alloy melt. After treatment, let it stand for 5 minutes, cool to 700°C, remove the slag, and then cast it. The casting molding process used is gravity casting, and the melt is cast into a metal mold preheated to 200°C to prepare a casting. The heat treatment process used for the ingot: the same as Example 1;

[0169] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0170] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0171] Comparative Example 2:

[0172] Comparative Example 2: Based on Comparative Example 1, a trace amount of Cu element is further added. The content of each element in the cast aluminum alloy is shown in Table 1 below in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0173] The specific steps include the following:

[0174] (1) The mass ratio of the alloy components in this example is shown in Table 1;

[0175] (2) The specific smelting steps of the alloy in this example include:

[0176] The weighed A356.2 alloy and pure Cu wire are melted at a melting temperature of 760°C. After all are melted, add a pure Mg block wrapped in aluminum foil, stir manually for 2 minutes to make the composition uniform, and let it stand and keep warm for 10 minutes. Cool the melt to 730°C and add AlSr10 intermediate alloy, cast the component mushroom sample, and after the composition is qualified, add Al-Ti-CB refiner and stir evenly. The amount of refiner added is 3‰ of the melt mass. At 730°C, the rotary argon injection method is used, and F-228 general refining agent is added externally to the alloy melt for refining and slag removal. The amount of refining agent added is 0.15% of the weight of the alloy melt. After treatment, let it stand for 5 minutes, cool to 700°C, remove the slag, and then cast it. The casting molding process used is gravity casting, and the melt is cast into a metal mold preheated to 200°C to prepare a casting. The heat treatment process used for the ingot: the same as Example 1;

[0177] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0178] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0179] Comparative Example 3:

[0180] Comparative Example 3 further increases the Fe content in the alloy on the basis of Comparative Example 2. The contents of each element in the cast aluminum alloy are shown in Table 1 below in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0181] The specific steps include the following:

[0182] (1) The mass ratio of alloy components in this example is shown in Table 1;

[0183] (2) The specific smelting steps of the alloy in this example include:

[0184] The weighed A356.2 alloy, pure Cu wire and AlFe10 intermediate alloy are melted at a melting temperature of 760°C. After all are melted, add a pure Mg block wrapped in aluminum foil, stir manually for 2 minutes to make the composition uniform, and let it stand and keep warm for 10 minutes. Cool the melt to 730°C and add AlSr10 intermediate alloy, cast the component mushroom sample, and after the composition is qualified, add Al-Ti-CB refiner and stir evenly. The amount of refiner added is 3‰ of the melt mass. At 730°C, the rotary argon injection method is used, and F-228 general refining agent is added externally to the alloy melt for refining and slag removal. The amount of refining agent added is 0.15% of the weight of the alloy melt. After treatment, let it stand for 5 minutes, cool to 700°C, remove the slag, and then cast it. The casting molding process used is gravity casting, and the melt is cast into a metal mold preheated to 200°C to prepare a casting. The heat treatment process used for the ingot: the same as Example 1;

[0185] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0186] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0187] Comparative Example 4:

[0188] Comparative Example 4 adds trace amounts of Mn, Cr, and Cu elements on the basis of Comparative Example 1 (but the Cu element content does not reach the scope of the present application). The content of each element in the cast aluminum alloy is shown in Table 1 in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0189] The specific steps include the following:

[0190] (1) The mass ratio of alloy components in this example is shown in Table 1;

[0191] (2) The specific smelting steps of the alloy in this example include:

[0192] The weighed A356.2 alloy, pure Cu wire, AlMn10 and AlCr10 master alloys were melted at a melting temperature of 760°C. After all were melted, pure Mg blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 730°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 730°C, the F-228 general refining agent was added to the alloy melt by the rotary argon injection method for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting molding process used was gravity casting, and the melt was cast into a metal mold preheated to 200°C to prepare castings. The heat treatment process used for the ingot is the same as that of Example 1;

[0193] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0194] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0195] Comparative Example 5:

[0196] The content of Cu element in Comparative Example 5 is higher than the upper limit of the present invention. The content of each element in the cast aluminum alloy is shown in Table 1 below in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0197] The specific steps include the following:

[0198] (1) The mass ratio of the alloy components in this example is shown in Table 1;

[0199] (2) The specific smelting steps of the alloy in this example include:

[0200] The weighed A356.2 alloy, Cu wire, AlMn10 and AlCr10 master alloys were melted at a melting temperature of 760°C. After all were melted, pure Mg blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 730°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 730°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting molding process used was gravity casting, and the melt was cast into a metal mold preheated to 200°C to prepare castings. The heat treatment process used for the ingot is the same as that of Example 1;

[0201] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0202] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0203] Comparative Example 6:

[0204] The content of Fe element in Comparative Example 6 is higher than the upper limit of the present invention. The content of each element in the cast aluminum alloy is shown in Table 1 below in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0205] The specific steps include the following:

[0206] (1) The mass ratio of the alloy components in this example is shown in Table 1;

[0207] (2) The specific smelting steps of the alloy in this example include:

[0208] The weighed A356.2 alloy, Cu wire, AlMn10, AlCr10 and AlFe10 master alloys were melted at a melting temperature of 760°C. After all were melted, pure Mg blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 730°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 730°C, the F-228 general refining agent was added to the alloy melt by rotary argon injection method for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then slag was removed, and then cast. The casting molding process used was gravity casting, and the melt was cast into a metal mold preheated to 200°C to prepare castings. The heat treatment process used for the ingot is the same as that of Example 1;

[0209] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0210] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0211] Comparative Example 7:

[0212] The content of Zr element in Comparative Example 7 is higher than the upper limit of the present invention. The content of each element in the cast aluminum alloy is shown in Table 1 below in terms of mass percentage, and the remainder is Al and other inevitable impurities except Fe.

[0213] The specific steps include the following:

[0214] (1) The mass ratio of alloy components in this example is shown in Table 1;

[0215] (2) The specific smelting steps of the alloy in this example include:

[0216] The weighed A356.2 alloy, Cu wire, AlMn10, AlCr10, AlZr10 and AlFe10 master alloys were melted at a melting temperature of 760°C. After all of them were melted, pure Mg blocks wrapped in aluminum foil were added, stirred manually for 2 minutes to make the composition uniform, and then left to stand for 10 minutes. The melt was cooled to 730°C and AlSr10 master alloy was added to cast the mushroom sample. After the composition was qualified, Al-Ti-CB refiner was added and stirred evenly. The amount of refiner added was 3‰ of the melt mass. At 730°C, the rotary argon injection method was used to add F-228 general refining agent to the alloy melt for refining and slag removal. The amount of refining agent added was 0.15% of the weight of the alloy melt. After treatment, it was left to stand for 5 minutes, cooled to 700°C, and then the slag was removed, and then cast. The casting process used is gravity casting, and the melt is cast into a metal mold preheated to 200°C to prepare a casting. The heat treatment process used for the ingot is the same as in Example 1;

[0217] After that, water quenching (cooling to room temperature in water within 30 seconds) + aging at 170°C for 8 hours, after cooling, samples were taken from the ingot for microstructure observation and performance testing.

[0218] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloy prepared in this example are shown in Table 2.

[0219] Comparative Example 8:

[0220] This comparative example is basically the same as Example 1, except that the heating rate of the heat treatment process is different, specifically:

[0221] The heating rate from room temperature to 250°C is 5°C / min;

[0222] The heating rate from 250°C to 325°C is 0.3°C / min;

[0223] The heating rate from 325°C to 450°C is 0.3°C / min;

[0224] The heating rate from 450°C to 530°C is 0.4°C / min.

[0225] That is, the heating rate in the fourth stage is not within the scope of the present invention.

[0226] Comparative Example 9:

[0227] This comparative example is basically the same as Example 1, except that the heating rate of the heat treatment process is different, specifically: the heating rate from room temperature to 250°C is 5°C / min;

[0228] The heating rate from 250°C to 325°C is 1.5°C / min;

[0229] The heating rate from 325°C to 450°C is 2.5°C / min;

[0230] The heating rate from 450°C to 530°C is 3.5°C / min.

[0231] That is, the second and third heating rates are not within the scope of the present invention.

[0232] Table 1 Examples and Comparative Examples Composition (where - represents none)

[0233]

[0234] The room temperature mechanical properties, corrosion properties, fatigue properties and microstructure results of the alloys prepared in various embodiments and comparative examples are shown in Table 2, wherein the blank grids represent the absence of the corresponding phase.

[0235] Table 2 Performance and organizational statistics of the examples and comparative examples

[0236]

[0237] From the results in Table 2, it can be seen that the A356 alloy currently used in Comparative Example 1 has lower strength and fatigue properties, but better corrosion resistance; after a trace amount of Cu is added in Comparative Example 2, the strength of the alloy is significantly improved compared with Comparative Example 1, but the corrosion resistance is reduced; by adding a trace amount of Mn and Cr elements on the basis of Comparative Example 2, the fatigue strength of the alloy in Example 1 is greatly improved compared with Comparative Examples 1 and 2, and the corrosion performance is not reduced, thereby obtaining an excellent combination of strength and toughness, fatigue performance and corrosion resistance; further, a trace amount of Sn element is added on the basis of Example 1, and the strength, toughness and corrosion resistance of the alloy in Example 2 are close to those in Example 1, but the fatigue strength is better than that in Example 1.

[0238] On the basis of implementation 1 and 2, the Fe content in the alloy was increased by 0.45%. Through microstructural observation, the area fraction of the iron phase in the microstructure of the alloy of Example 3 was significantly increased compared with that of Examples 1 and 2, but the iron phase morphology was still granular, Chinese character-shaped, etc., and no obvious needle-shaped iron-rich phase was found. Through mechanical property testing, the strength and elongation of the alloy did not decrease significantly, and good plasticity was maintained. The corrosion resistance of the alloy did not decrease significantly, and the fatigue strength was still significantly better than that of the A356 alloy with low iron content. When the Fe content in Comparative Example 3 reached 0.3%, and no trace Mn and Cr elements were added, it was found through organizational observation that the iron phase inside the alloy Most of them are needle-shaped, and the area percentage is significantly increased compared with Comparative Examples 1 and 2. Mechanical properties tests show that the tensile strength and elongation of the alloy are significantly reduced; when the iron content in the alloy is increased to 0.7%, obvious needle-shaped iron-rich phases appear in the microstructure of the alloy of Comparative Example 6, indicating that the regulating effect of the Mn and Cr elements in the system has decayed. Mechanical properties tests show that the tensile strength and elongation of the alloy are significantly reduced, and the fatigue performance is significantly reduced. The main reason is that when the Fe content is too high, the regulating effect of trace Mn and Cr elements is decayed, and more needle-shaped phases that are prone to stress concentration are formed in the alloy, resulting in the deterioration of strength, toughness and fatigue performance.

[0239] Compared with Example 1, no trace Cu element is added in Comparative Example 4. After microstructural observation, the iron phase morphology in the alloy microstructure is similar to that in Example 1 in granular and Chinese character shapes, etc., and no obvious needle-shaped iron-rich phase is found. Submicron-level α-dispersed phase is precipitated in the crystal, but its average size is larger than that in Example 1. After mechanical property testing, the static mechanical properties of the alloy are significantly lower than those in Example 1, and the static mechanical properties are close to those of the A356 alloy in Comparative Example 1, and the fatigue performance is better. Compared with Example 1, the Cu content of the alloy in Comparative Example 5 is increased to 0.7%. After microstructural observation, the iron phase morphology in the alloy microstructure is similar to that in Example 1 in granular and Chinese character shapes, etc., and no obvious needle-shaped iron-rich phase is found. Submicron-level α-dispersed phase is precipitated in the crystal. After mechanical property testing, it is found that the alloy is slightly improved compared with Example 1, but the corrosion resistance is significantly reduced.

[0240] In Example 4, a trace amount of Zr element is added to the alloy based on Examples 1, 2, and 3. Through microstructural observation, the iron phase in the alloy is granular, Chinese character-shaped, etc., and no obvious needle-shaped iron-rich phase and AlSiTiZr primary phase are found. The number of submicron dispersed phases inside the grains is significantly increased. After transmission electron microscopy observation, it is found that there are two types of dispersed phases with obvious differences in morphology in the crystal, namely polygonal α-AlSiFeMnCr and short rod-shaped / rod-shaped (Al,Si)3(Zr,Ti) dispersed phases. Mechanical property tests show that the static mechanical properties of the alloy are slightly improved, and the fatigue performance is excellent. Corrosion resistance tests show that the corrosion resistance of the alloy is equivalent to that of Examples 1, 2, and 3, and an excellent combination of strength and toughness, fatigue performance, and corrosion resistance is obtained. Comparative Example 7 Compared with Example 4, the Zr content in the alloy reaches 0.32%. Through structural observation, the iron phase in the alloy is granular, Chinese character-shaped, etc., and needle-shaped AlSiTiZr primary phase clusters (such as Figure 2 ), the number of submicron dispersed phases inside the grains further increased. After transmission electron microscopy observation, it was found that there were two types of dispersed phases with obvious differences in morphology in the crystal, namely polygonal α-AlSiFeMnCr and short rod-shaped / rod-shaped (Al,Si)3(Zr,Ti) dispersed phases. Mechanical properties tests found that the static strength of the alloy was slightly improved, but the elongation was significantly deteriorated. Fatigue properties tests found that the fatigue properties of the alloy were slightly lower than those of Example 4.

[0241] Example 5 adds a trace amount of Mo element compared to Example 4. Microstructural observation shows that part of the iron-rich phase in the alloy is transformed into fine spherical particles. The iron phase morphology in the alloy is mainly spherical, granular, and Chinese character-shaped. No obvious needle-shaped iron-rich phase and AlSiTiZr primary phase are found. The number of submicron dispersed phases inside the grains is significantly increased. Transmission electron microscopy observation shows that there are two types of dispersed phases with obvious differences in morphology in the crystals, namely polygonal α-AlSiFeMnCrMo and short rod-shaped / rod-shaped (Al,Si)3(Zr,Ti) dispersed phases. Mechanical properties and corrosion resistance tests show that the alloy has an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0242] Example 6 adds a trace amount of V element on the basis of Example 2. Microstructural observation shows that part of the iron-rich phase in the alloy is transformed into fine spherical particles. The iron phase morphology in the alloy is mainly spherical, granular, Chinese character-shaped, etc. No obvious needle-shaped iron-rich phase is found. The number of submicron dispersed phases inside the grains is significantly increased. Transmission electron microscopy observation shows that there are two types of dispersed phases with obvious differences in morphology in the crystal, namely polygonal α-AlSiFeMnCrV and short rod-shaped / rod-shaped (Al,Si)3(Ti,V) dispersed phases. Mechanical properties and corrosion resistance tests show that the alloy has an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0243] Example 7 adds a trace amount of Zr element on the basis of Example 6. Through microstructural observation, it is found that part of the iron-rich phase in the alloy is transformed into small spherical particles. The morphology of the iron phase in the alloy is mainly spherical, granular, Chinese character-shaped, etc. No obvious needle-shaped iron-rich phase and AlSiTiZr phase are found. The number of submicron dispersed phases inside the grains is significantly increased. After transmission electron microscopy observation, it is found that there are two types of dispersed phases with obvious differences in morphology in the crystal, namely polygonal α-AlSiFeMnCrV and short rod-shaped / rod-shaped (Al,Si)3(Ti,Zr,V) dispersed phases. Mechanical properties and corrosion resistance tests show that the alloy has an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0244] Example 8 adds trace amounts of Y and Er elements on the basis of Example 4. Through microstructural observation, the iron phase in the alloy is granular, Chinese character-shaped, etc., and no obvious needle-shaped iron-rich phase and AlSiTiZr primary phase are found. The number of submicron dispersed phases inside the grains is significantly increased. After transmission electron microscopy observation, it is found that there are two types of dispersed phases with obvious differences in morphology in the crystal, namely polygonal α-AlSiFeMnCrV and short rod-shaped / rod-shaped (Al,Si)3(Ti,Zr,Y,Er) dispersed phases. Mechanical properties and corrosion resistance tests show that the alloy has an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0245] In Example 9, the trace element V was used to replace the Cr element in Example 4. Microstructural observation showed that part of the iron-rich phase in the alloy was transformed into fine spherical particles. The iron phase in the alloy was mainly spherical, granular, and Chinese character-shaped. No obvious needle-shaped iron-rich phase and AlSiTiZr phase were found. The number of submicron dispersed phases inside the grains was similar. Transmission electron microscopy observation showed that there were two types of dispersed phases with obvious differences in morphology in the crystals, namely polygonal α-AlSiFeMnV and short rod-shaped / rod-shaped (Al,Si)3(Ti,Zr,V) dispersed phases. Mechanical properties and corrosion resistance tests showed that the alloy had an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0246] From the performance results of Examples 1 to 9 in the present invention compared with Comparative Examples 1 to 7, it can be seen that the alloy and preparation method of this patent can significantly improve the strength and fatigue resistance of the cast aluminum alloy material, while maintaining good corrosion resistance, and obtain an excellent combination of strength and toughness, fatigue performance and corrosion resistance.

[0247] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0248] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A cast aluminum alloy, comprising Al, Si, Cu, Mg, Mn, Ti, Cr, Sr and unavoidable impurities, wherein the impurities include Fe and other impurities except Fe, characterized in that: In terms of mass percentage, the cast aluminum alloy comprises: Si 3%-9%, Cu 0.1%-0.45%, Mg 0.1%-0.5%, Mn 0.05%-0.4%, Cr 0.05%-0.3%, Ti 0.05%-0.3%, Sr 0.005%-0.04%, Fe is less than or equal to 0.5%, and the sum of other impurities except Fe is not more than 0.2%. The Al content is adjusted so that the total amount of the aluminum alloy is 100%. The process of preparing the cast aluminum alloy includes the steps of mixing and melting the components and then refining them, then making an aluminum alloy ingot, and heat treating the aluminum alloy ingot; the heat treatment is carried out from room temperature to an end temperature, and the end temperature is 515-540°C; and when the temperature is from room temperature to 250°C, the heating rate is controlled to be 0.5-10°C / min; when the temperature is from 250°C to 325°C, the heating rate is controlled to be 0.1-1.25°C / min; when the temperature is from 325°C to 450°C, the heating rate is controlled to be 0.1-2°C / min; when the temperature is from 450°C to the end temperature, the heating rate is controlled to be 0.5-10°C / min.

2. The cast aluminum alloy according to claim 1, characterized in that In the process of preparing the cast aluminum alloy, the heating rate from 450°C to the end temperature is controlled to be greater than the heating rate from 250°C to 325°C, and the heating rate from 450°C to the end temperature is controlled to be greater than the heating rate from 325°C to 450°C.

3. The cast aluminum alloy according to claim 1, characterized in that: In terms of mass percentage, Fe accounts for 0.1%-0.5% in the cast aluminum alloy; and / or, some components including Al in the cast aluminum alloy are added by adding recycled aluminum alloy, and the recycled aluminum alloy is a combination of one or more selected from Al-Si-Mg alloy, Al-Si-Cu alloy, Al-Si-Cu-Mg alloy, and Al-Mn alloy.

4. The cast aluminum alloy according to claim 1, characterized in that: The cast aluminum alloy also includes Zr. After the heat treatment, the interior of the alloy α-Al grains includes (Al, Si) 3 (Zr) and (Al, Si) 3 (Zr, Ti) dispersed phases.

5. The cast aluminum alloy according to claim 4, characterized in that: In terms of mass percentage, Zr accounts for 0.05%-0.3% in the cast aluminum alloy.

6. The cast aluminum alloy according to claim 1, characterized in that: The cast aluminum alloy further includes X1, and X1 is Sn and / or In.

7. The cast aluminum alloy according to claim 6, characterized in that: In terms of mass percentage, in the cast aluminum alloy, the content of the elements contained in X1 is independently 0.001%-0.2%.

8. The cast aluminum alloy according to claim 1, characterized in that: The cast aluminum alloy further includes X2, wherein X2 is a combination of one or more selected from Mo, V, Y and Er.

9. The cast aluminum alloy according to claim 8, characterized in that: In terms of mass percentage, in the cast aluminum alloy, the content of the elements contained in X2 is independently 0.01%-0.3%.

10. The cast aluminum alloy according to claim 1, characterized in that The alloy structure of the cast aluminum alloy includes rose-shaped α-Al grains, dendrite-shaped α-Al grains, micron-sized spherical eutectic silicon particles, micron-sized granular iron-containing intermetallic compounds, and micron-sized Chinese character-shaped iron-containing intermetallic compounds; The rose-shaped α-Al grains and dendrite-shaped α-Al grains contain α-type dispersed phases with a size of 50 to 500 nm, rod-shaped Al3M-type dispersed phases with a diameter of 20 to 50 nm, and β″ phases, β′ phases and Q′ phases that are coherent or semi-coherent with the matrix; The sizes of the micron-sized granular iron-containing intermetallic compound and the micron-sized Chinese character-shaped iron-containing intermetallic compound are both 2 μm to 25 μm.

11. The cast aluminum alloy according to claim 1, characterized in that The cast aluminum alloy has a yield strength of 270-290 MPa, a tensile strength of 330-360 MPa and an elongation after fracture of 8%-12% at room temperature.

12. The cast aluminum alloy according to claim 1, characterized in that Under the test conditions of smooth specimen, stress ratio R of -1, and 10 million cycles, the fatigue strength of the cast aluminum alloy is 110-120 MPa.

13. The cast aluminum alloy according to claim 1, characterized in that The process of preparing the cast aluminum alloy also includes the step of heating to the end point temperature and then maintaining the temperature at the end point temperature for 4-16 hours.

14. A method for preparing the cast aluminum alloy according to any one of claims 1 to 13, characterized in that: The preparation method comprises: The ingredients are prepared according to the composition, melted, refined, metamorphosed and refined to form an aluminum alloy ingot, and the aluminum alloy ingot is subjected to heat treatment, quenching cooling and aging treatment; wherein the heat treatment is carried out from room temperature to the end temperature, and the end temperature is 515-540°C; and from room temperature to 250°C, the heating rate is controlled to be 0.5-10°C / min; from 250°C to 325°C, the heating rate is controlled to be 0.1-1.25°C / min; from 325°C to 450°C, the heating rate is controlled to be 0.1-2°C / min; from 450°C to 520°C, the heating rate is controlled to be 0.5-10°C / min; from 450°C to the end temperature, the heating rate is controlled to be 0.5-10°C / min.

15. The preparation method according to claim 14, characterized in that: The heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 250°C to 325°C, and the heating rate from 450°C to the final temperature is controlled to be greater than the heating rate from 325°C to 450°C.

16. The preparation method according to claim 14, characterized in that: After heating to the end point temperature, the temperature is kept at the end point temperature for 4-16 hours, and then the quenching cooling is performed.

17. The preparation method according to claim 14, characterized in that: The quenching cooling is cooling to room temperature in water within 30 seconds; and / or the aging treatment is keeping warm at 140-200°C for 6-18 hours.

18. Use of the cast aluminum alloy according to any one of claims 1 to 13 in the preparation of automobile chassis structural parts, engines or transmission components.

Citation Information

Patent Citations

  • Cast aluminum alloy and preparation method and application thereof

    CN117488148A

Cited By

  • Aluminum-lithium alloy heat treatment method and ribbed cylindrical shell

    CN120138529A

  • Aluminum-lithium alloy heat treatment method and ribbed cylindrical shell

    CN120138529B